Evaluation of Platelet-rich Fibrin (PRF) and Titanium-prepared Platelet-rich Fibrin (T-PRF) in treatment of Endo-perio Lesions. A comparative study - Thakur, Suyash; Ansari, Afsana; Behera, Subasish; S, Aswathy; Nanda, Soumyaranjan (Journal of Neonatal Surgery, 2025)
Background: Endo-perio lesions pose a significant challenge in dental practice due to their complex etiology and treatment approach. Platelet-rich fibrin (PRF) and titanium-prepared platelet-rich fibrin (T-PRF) have gained attention for their regenerative potential in periodontal and endodontic therapy. This study aims to compare the clinical efficacy of PRF and T-PRF in the management of endo-perio lesions. Materials and Methods: A total of 30 patients with endo-perio lesions were randomly assigned into two groups: Group A (PRF) and Group B (T-PRF), with 15 patients in each group. Following standard endodontic treatment, PRF or T-PRF was placed in the defect site, and clinical parameters including probing depth (PD), clinical attachment level (CAL), and radiographic bone density were evaluated at baseline, 3 months, and 6 months. Statistical analysis was performed using paired t-tests and ANOVA to compare the results within and between groups. Results: Both groups showed significant improvement in clinical parameters over time. In Group A (PRF), PD reduced from 6.5 ± 1.2 mm at baseline to 3.8 ± 0.9 mm at 6 months, while in Group B (T-PRF), PD reduced from 6.7 ± 1.1 mm to 3.2 ± 0.8 mm. CAL gain was also greater in the T-PRF group (2.9 ± 0.6 mm) compared to the PRF group (2.3 ± 0.5 mm). Radiographic analysis revealed a higher increase in bone density in the T-PRF group. The intergroup comparison showed statistically significant differences favoring T-PRF (p < 0.05). Conclusion: Both PRF and T-PRF were effective in managing endo-perio lesions, with T-PRF demonstrating superior outcomes in terms of periodontal regeneration and bone density improvement. T-PRF can be considered a promising biomaterial for enhanced healing in endo-perio lesions.